A STUDY ON THE EFFECT PRESCHOOLER-TEACHER RELATIONSHIP ON SOCIAL SKILL LEVELS OF PRESCHOOLERS - Devlet ALAKOÇ PİRPİR (Fırat University, 2019)
This study was conducted to evaluate the effect preschooler-teacher relatıonship on social skill levels of preschoolers. A relational survey was carried out between dependent and independent variables in this survey type of study. Along with their teachers, 348 preschoolers from low and high SES attending independent preschools affiliated with Ministry of National Education in province center of Sivas during 2012-2013 school year. As data collection tools, the current study used two instruments: the first was a 28-item standard rating scale titled theStudent-TeacherRelationshipScale used to evaluate teachers’ perception of their in